Comparison of saline infusion test and captopril challenge test in the diagnosis of Chinese with primary aldosteronism in different age groups - Sun, Kaiwen; Gong, Minghui; Yu, Yang; Yang, Minghui; Zhang, Ying; Jiang, Yinong; Song, Wei (Frontiers in Endocrinology, 2024)
Background: To explore the diagnostic accuracy and the optimal cut-off value between the saline infusion test (SIT) and captopril challenge test (CCT) (including the value and suppression of plasma aldosterone concentration (PAC)) for primary aldosteronism (PA) diagnosing.Methods: A total of 318 patients with hypertension were consecutive enrolled including 126 patients with PA and 192 patients with essential hypertension (EH) in this observational study. The characteristics of patients and laboratory examinations were collected and compared. The comparison between SIT and CCT was carried by drawing receiver operator characteristic curve (ROC) and calculating area under the curve (AUC) to explore the diagnostic accuracy and the optimal cut-off value.The average age was 51.59±10.43 in PA group and 45.72±12.44 in EH group (P<0.05). The optimal cut-off value was 10.7 ng/dL for post-CCT PAC, 6.8 ng/dL for post-SIT PAC and 26.9% for suppression of post-CCT PAC. The diagnostic value of post-CCT PAC was the highest with 0.831 for the AUC and 0.552 for the Youden index. The optimal cut-off value for patients who were less than 50 years old was 11.5 ng/dL for post-CCT PAC and 8.4 ng/dL for post-SIT PAC. The suppression of post-CCT PAC turned to 18.2% for those of age 50 or older.Compared with SIT, CCT had a higher diagnostic value when post-CCT PAC was used as the diagnostic criterion in Chinese people, while the selection of diagnostic thresholds depended on patient age.